Perancangan Interior Pusat Kebugaran Jasmani Anak di Surabaya - Hardjawikarta, Jovita (Intra, 2014)
This design project is about a Sport Centre for Children. The background of the birth of this idea is that children can get an education in Surabaya completely and perfectly, not only intellectually increase in intelligence but also can develop in motor development that can help children to be more confident and Â have a healthy lifestyle since the early age. The theme of this design is "Garden" Â by creating an atmosphere of a garden in the room so that children can feel more free to express and also not saturated. The design is equipped with classrooms Gymnastics, Dance Class, Yoga Class, Archery Class, Karate Class, Indoor Basketball, Indoor soccer, Indoor Hockey, and supported with a shower room, locker room, lobby, play ground and a cafe.